2021
DOI: 10.3390/su13073972
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Mitigate Power Imbalances in Collaborative Environmental Governance? Examining the Role of the Village Facilitation Team Approach Observed in West Kalimantan, Indonesia

Abstract: Researchers have focused on collaborative governance as an effective measure to realise sustainable natural resource management through the participation of various stakeholders. However, the literature has indicated that issues such as power imbalances tend to undermine the effectiveness of collaborative governance. Powerful actors represented by the government tend to control collaborative processes and produce benefits for dominant groups, while less empowered local communities are often deprived of opportu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Finally, in line with previous research highlighting how power imbalances can discourage actors from engaging in communication in intractable conflicts (e.g., Arai et al 2021 ; Baker and Chapin III 2018 ; Raitio 2013 ), the study found that the mine permitting system inhibited reframing by failing to provide sufficient incentives for the mine opponents to engage with their disputants. Specifically, because the mine opponents felt that they had few or no opportunities to advance their positions in the formal system, many considered informal actions and intragroup mobilization as more meaningful than engaging with their disputants in the permit process (e.g., through participating in corporate consultation).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Finally, in line with previous research highlighting how power imbalances can discourage actors from engaging in communication in intractable conflicts (e.g., Arai et al 2021 ; Baker and Chapin III 2018 ; Raitio 2013 ), the study found that the mine permitting system inhibited reframing by failing to provide sufficient incentives for the mine opponents to engage with their disputants. Specifically, because the mine opponents felt that they had few or no opportunities to advance their positions in the formal system, many considered informal actions and intragroup mobilization as more meaningful than engaging with their disputants in the permit process (e.g., through participating in corporate consultation).…”
Section: Discussionsupporting
confidence: 87%
“…For example, when frame inconsistences occur, engagement with alternative frames is often necessary, making reciprocal communication more probable (Laws and Rein 2003 ). Research has also found that meaningful intergroup communication sometimes hinges on contextual changes that level power imbalances and incentivize disputants to engage with each other (Arai et al 2021 ). These can include external shocks, such as environmental disasters, that awaken the disputants to the risks and uncertainties of non-collaboration (Montambeault et al 2020 ).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The literature emphasizes power as a determinant of stakeholder collaboration for sustainability. However, power is largely discussed from the perspective of its imbalance [ 87 ] or even abuse [ 88 ]. This current study adds to the body of knowledge by indicating a new notion of power i.e., ‘powerful as individuals but powerless when together’ (TB5).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Asymmetries in expertise are even required for learning to take place (Rogoff, 1990;Vygotsky, 1978). However, collaboration can help build trust, even when there is a risk of power imbalance (Arai et al, 2021;Sheriff et al, 2019). We saw this reflected in students' experiences of valuable conversations both with the instructor of the course, and with their peers, where despite the asymmetry in expertise, students felt like equal participants in their learning.…”
Section: Trauma-informed Principles As Mutually Reinforcingmentioning
confidence: 96%